(untitled) - Sarnes, Risa (Cần Thơ, 2019)
This research aimed to establish the optimum concentration of sorbitol (1.32-4.68%), STPP (0.32-3.68%) and NaCl (1.32-4.68%) by response surface methodology and optimum soaking time of 15-60 min. The optimized condition for soaking was NaCl 1.32%, STPP 1.88% and sorbitol 4.68% for 30 minutes which give a significant effect (p<0.05) to the yield and impovement in the sensory of treated fillet.
Keywords: Fishery processing,Chế biến thủy sản